Strain-durable dark current in near-infrared organic photodetectors for skin-conformal photoplethysmographic sensors - Eun, Hyeong Ju; Lee, Hanbee; Shim, Yeongseok; Seo, Gyeong Uk; Lee, Ah Young; Park, Jong Jin; Heo, Junseok; Park, Sungjun; Kim, Jong H. (iScience, 2022)
Sensitive detection of near-infrared (NIR) light is applicable to variety of optical, chemical, and biomedical sensors. Of these diverse applications, NIR photodetectors have been used as a key component for photoplethysmography (PPG) sensors. In particular, because NIR organic photodetectors (OPDs) enable fabrication of stretchable and skin-conformal PPG sensors, they are attaining tremendously increasing interest in both academia and industry. Herein, we report strain-durable and highly sensitive NIR OPDs using an organic bulk heterojunction (BHJ) layer. For effective suppression of dark current, we employed BHJ combination consisting of PTB7-Th:Y6 which forms high energy barrier against transport-injected holes. The optimized OPDs exhibited high specific detectivity up to 2.2 × 1012 Jones at 800 nm. By constructing the devices on the parylene substrates, we successfully demonstrated stretchable NIR OPDs and high-performance skin-conformal PPG sensors.
Keywords: Applied sciences; Sensor; Wearable computing